Comparison of Quality of Life Before and After Septoplasty With Short Form-36. Issue 3 (May 2020) - Erdivanli, Ozlem Celebi; Coskun, Zerrin Ozergin; Ozgur, Abdulkadir; Ogurlu, Mahmut; Demirci, Munir; Dursun, Engin
Abstract : Abstract: The authors aimed to evaluate quality of life after septal surgery with Short Form-36 survey, and the effectiveness of the survey. Nasal symptoms (nasal obstruction, facial pain, catarrh), and general quality of life (using the Turkish version of the Short Form-36 questionnaire) were assessed preoperatively and at 1st and 6th postoperative months. Acoustic rhinometry and rhinomanometry were assessed preoperatively and at 6th postoperative month. Data from 78 patients were analyzed. This prospective clinical study was conducted on patients complaining of nasal obstruction with nasal septal deviation. Seventy-eight patients were included in the study. Fourty-two patients (53.8%) were male and 36 patients (46.2%) were female. At 1st postoperative month, nasal obstruction, facial pain and catarrh scores significantly improved in all, 46, 18 patients, respectively ( P  < 0.0001). At 6th postoperative month, scores nonsignificantly worsened by 1 point in 12, 6, 12 patients, respectively. Nasal volume significantly increased and total resistance significantly decreased at 6th month ( P  < 0.0001). Compared to preoperative values, all items except social function and bodily pain significantly increased at 1st postoperative month. Compared to values at 1st postoperative month, only bodily pain score decreased at 6th postoperative month. One patient presented with septal perforation. Septoplasty is a well-established technique to reduce nasal obstruction and improve quality of life. SF-36 may be used as a reliable measure of changes in quality of life after septal surgery. Abstract : Supplemental Digital Content is available in the text